Repeated-Dose Toxicity, Biodistribution, and Shedding Assessments With a ChAd155 Respiratory Syncytial Virus Vaccine Candidate Evaluated in Rabbits and Rats. (August 2022) - Stokes, Alan H.; Planty, Camille; Pion, Johanne; Ancian, Philippe; Rogue, Alexandra; Bansard, Carine; Silvano, Jérémy; Papineau, Dominique; Ben Abdeljelil, Nawel; Maruggi, Giulietta; Song, Haifeng; Spickler, Catherine; et al.
Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections (LRTI) in infants, and toddlers and vaccines are not yet available. A pediatric RSV vaccine (ChAd155-RSV) is being developed to protect infants against RSV disease. The ChAd155-RSV vaccine consists of a recombinant replication-deficient chimpanzee-derived adenovirus (ChAd) group C vector engineered to express the RSV antigens F, N, and M2-1. The local and systemic effects of three bi-weekly intramuscular injections of the ChAd155-RSV vaccine was tested in a repeated-dose toxicity study in rabbits. After three intramuscular doses, the ChAd155-RSV vaccine was considered well-tolerated. Changes due to the vaccine-elicited inflammatory reaction/immune response were observed along with transient decreases in platelet count without physiological consequences, already reported for other adenovirus-based vaccines. In addition, the biodistribution and shedding of ChAd155-RSV were also characterized in two studies in rats. The distribution and persistence of the ChAd155-RSV vaccine candidate was consistent with other similar adenovector-based vaccines, with quantifiable levels of ChAd155-RSV observed at the injection site (muscle) and the draining lymph nodes up to 69 days post administration. The shedding results demonstrated that ChAd155-RSV was generally not detectable in any secretions or excreta samples. In conclusion, the ChAd155-RSV vaccine was well-tolerated locally and systemically.